Considering the Cellular Composition of Olfactory Ensheathing Cell Transplants for Spinal Cord Injury Repair: A Review of the Literature - Miah, Mahjabeen; Ferretti, Patrizia; Choi, David (Frontiers in Cellular Neuroscience, 2021)
Olfactory ensheathing cells (OECs) are specialized glia cells of the olfactory system that support the continual regeneration of olfactory neurons throughout adulthood. Owing to their pro-regenerative properties, OECs have been transplanted in animal models of spinal cord injuries (SCI) and trialed in clinical studies on SCI patients. Although these studies have provided convincing evidence to support the continued development of OEC transplantation as a treatment option for the repair of SCI, discrepancies in the reported outcome has shown that OEC transplantation requires further improvement. Much of the variability in the reparative potential of OEC transplants is due to the variations in the cell composition of transplants between studies. As a result, the optimal cell preparation is currently a subject of debate. Here we review, the characterization as well as the effect of the cell composition of olfactory cell transplantation on therapeutic outcome in SCI. Firstly, we summarize and review the cell composition of olfactory cell preparations across the different species studied prior to transplantation. Since the purity of cells in olfactory transplants might affect the study outcome we also examine the effect of the proportions of OECs and the different cell types identified on neuroregeneration. Finally, we consider the effect of the yield of cells on neuroregeneration by assessing the cell dose of transplants on therapeutic outcome. These are important factors that must be optimized in the clinical translation of OEC transplants.